Course Materials and Textbook Selection Criteria of English Language Teachers - Şahin, Münir (Muş Alparslan Üniversitesi, 2021)
ÖZBu çalışmada farklı okul düzeylerinde görev yapan İngilizce öğretmenlerinin ders materyali ve ders kitaplarının seçiminde kullandıkları kriterlerin neler olduğunu ve farklı düzeyler arasında ders materyali seçiminde benzerlikler ve farklılıkların neler olduğu belirlenmeye çalışılmıştır. Çalışma betimsel bir çalışma olmakla beraber nitel araştırma desenlerinden olgubilim desenine uygun olarak yapılmıştır. Çalışma öncesinde Tokat Gaziosmanpaşa Üniversitesi Sosyal ve Beşeri Bilimler Etik Kurulunun, 21 Mayıs 2021 tarihli E-33490967-044-41105 sayılı 11. oturumunun 18. karar numarası ile yazılı izni alınmıştır. Çalışmanın katılımcılarını 15 ilkokul, 17 ortaokul ve 19 lise olmak üzere toplan 51 İngilizce öğretmeni oluşturmaktadır. Yarı yapılandırılmış bir rehber görüşme formu kullanılarak katılımcıların görüşleri alınmış, katılımcılardan elde edilen veriler kod ve temalar oluşturacak şekilde içerik analizi yapılmış ve tablolara dönüştürülmüştür. Çalışmadan elde edilen bulgulara göre ders materyale seçiminde okul düzeyi fark etmeksizin “görsel zenginlik” katılımcıların çoğunluğu tarafından (f=36) kabul edilen ölçüt olmuştur. İngilizce öğretmenlerinin ders kitabı seçim kriterlerine ilişkin olarak ilk ve ortaöğretimde görsellik öncelikli ölçüt olarak belirtilirken, lise düzeyinde çalışan öğretmenlerini konuların anlatım şekline daha fazla dikkat ettikleri görülmüştür. Öğretmenler ders kitabı seçerken öğrencilerin yaş, cinsiyet, ilgi ve dil öğrenme amaçlarını göz önünde bulundurmalıdırlar.

In this study, it was tried to determine what the criteria used by English teachers working at different school levels in the selection of course materials and textbooks, and what the similarities and differences were in the selection of course materials between different levels. Although the study is a descriptive study, it was carried out in accordance with the phenomenological research pattern, one of the qualitative research designs. Prior to the study, written consent was obtained from the Gaziosmanpasa University Social and Humanity Studies Committee with Meeting decision number 11.18 on 21.05. 2021 and Protocol Number: E-33490967-044-41105. The participants of the study consist of 51 English language teachers, 15 from primary, 17 from secondary, and 19 from high schools. The opinions of the participants were taken by using a semi-structured guided interview form. Content analysis of the data obtained from the participants were done in a way to create codes and themes, and they were transformed into tables. According to the findings obtained from the study, "visual richness" was the criterion used by the majority of the participants (f=36), regardless of the level in the selection of course materials. Secondly, while primary school teachers prefer fun and up-to-date materials, it is seen that secondary school teachers pay attention to age-appropriateness and entertaining materials. It was observed that participants working at high school level with different priorities expressed similar views. Regarding the textbook selection criteria of English language teachers, visuality was stated as the primary criterion in primary and secondary education, while teachers working at the high school level paid more attention to the way the subjects were taught. The teachers should pay attention to students’ ages, genders, levels, interests and goals in language learning while choosing textbooks.
İngilizce Öğretmenlerinin Ders Materyali ve Ders Kitabi Seçim Kriterleri
anemon
Keywords: Ders kitabı seçim kriterleri; İngilizce ders kitapları; Ders materyalleri; Yabancı dil öğretmenleri; Textbook selection criteria; ELT books; Course materials; ELT teachers